Vitamin E composition of walnuts (Juglans regia L.): A 3-year comparative study of different cultivars. - Amaral, Joana S. (2008)
The tocopherol and tocotrienol composition of walnuts (Juglans regia L.) was determined for nine cultivars (cvs. Arco, Franquette, Hartley, Lara, Marbot, Mayette, Mellanaise, Parisienne, and Rego). Walnuts were harvested over three consecutive years from two different geographical origins (Bragancüa and Coimbra, Portugal), for a total of 26 samples. The methodology employed was a normal-phase high-performance liquid chromatography coupled to a series arrangement of a diode array detector followed by a fluorescence detector, allowing the simultaneous analysis of all tocopherols and tocotrienols. The analyses showed that all samples presented a similar qualitative profile composed of five compounds: R-tocopherol, â-tocopherol, ç-tocopherol, ä-tocopherol, and ç-tocotrienol. ç-Tocopherol was the major compound in all samples, ranging from 172.6 to 262.0 mg/kg, followed by R- and ä-tocopherols, ranging from 8.7 to 16.6 mg/kg and from 8.2 to 16.9 mg/kg, respectively. Multivariate analysis of the data obtained showed the existence of significant differences in composition among cultivars. These differences were also significant when cultivars were grouped by year of production, showing that besides genetic factors, the vitamin E composition was influenced by environmental factors.